Spectrophotometry and Histological Staining Potential of Ethanol Extract of brassica Oleracea (Red Cabbage) on Selected Organs of Sprague Dawley rat - E. Eyo, Esther; Udonkang, Mfoniso I.; Inyang, Imeobong J.; Umunnakwe, Leonard O.; Eworo, Raymond (Asian Journal of Pharmaceutical Research and Development, 2024)
Objective: Plants with coloring and dyeing effects have widely been used in histological staining. Natural dyes are less expensive, nontoxic, renewable and sustainable resources, with minimal environmental impact compared to synthetic stains. Red cabbage is one of such natural dyes. The red color of the red cabbage derived from anthocyanin pigments confers a great advantage to red cabbage. In this study, the physiochemical and spectrophotometric characteristics of red cabbage as well as its histological staining potentials on various tissues were carried out to determine its tissue specificity. Methods:The ethanol extract of red cabbage was prepared using 100% ethanol, then pH, spectrophotometry, and concentration of the red cabbage ethanol extract were measured before the solution was divided into two equal volumes, and one part was added with 2ml glacial acetic acid while the other part was added with 10g of aluminum sulfate. The two solutions were used to stain 10% neutral-buffered formalin-fixed, paraffin-wax-embedded tissue sections separately. Stained sections were viewed with a photomicroscope. Results: The ethanol extract was acidic at a pH of 4.89 and the spectrophotometry graph showed 3 peak absorbances at the wavelengths of 395nm, 545nm and 670nm. The maximum absorbance was 0.795 at the wavelength of 395nm and this is indicative of the pigment cyanidin which is the anthocyanin present in red cabbage. The red cabbage ethanol extract with both glacial acetic acid and aluminum sulfate showed good histological details in tissues of kidney, stomach, lungs, liver, spleen, small intestine and skin. There was no difference between the red cabbage ethanol extract and the conventional hematoxylin and eosin stain (P>0.05). Our study showed that red cabbage ethanol extract with acetic acid and aluminum sulfate is stable at 4oC, with color amber to light gold with a pH of 4.89 and a concentration of 1000 which gave good histological details. In general, our result indicates that red cabbage ethanol extract is an efficient stain for histological tissue structures and can be used as an eco-friendly alternative to eosin. Conclusion: Red cabbage ethanol extract stained basic structures of the cell such as the cytoplasm, muscle fibers and mucins. Therefore, red cabbage ethanol extract can be used in histological staining when appropriate modifications are done.